Cw laser oscillations in Cd II in an electron beam created plasma - Meyer, J. D., author; Rocca, Jorge J., author; Collins, G. J., author; North-Holland, publisher (Colorado State University. Libraries, 1982)
A cw Cd II laser has been demonstrated using electron beam excitation. Cw laser oscillation has been obtained on six transitions of Cd 11 in a He-Cd plasma. Output power as a function of electron beam discharge parameters has been investigated.